Discursive Construction of Political Categories and Moral Fields: God Versus Rights and Access in a Reproductive Health Legislative Debate - Montiel, Cristina Jayme (Archīum Ateneo, 2015)
Using a discursive lens, we argue that politicians rhetorically construct categories, storylines, and moral fields. We further claim that such discursive products are action‐oriented toward gaining popular support in a public sphere that is politically fault lined along similar moral orders. As a case in point, we analyze speeches delivered during congressional voting on a Reproductive Health bill (RH bill). Employing a mixed methods strategy, we first implement a quantitative lexical analysis of frequently used words, followed by a qualitative detection of cohering storylines on both sides of the debate. Results show that oppositionists mark their speeches with a deployment of the word God, while bill supporters use the word access conspicuously. One storyline claims that The RH bill stands against God, while the other purports that The RH bill advocates rights and access. Although both storylines assert moral righteousness, they invoke two different moral orders backed by power blocs and the public at large. The God story appeals to a Catholic discourse and the moral order loudly supported by the politically powerful Catholic Bishops Conference of the Philippines. The rights/access narrative references a liberal morality frame maintained by social liberals and Philippine President Aquino. We end our paper by introducing the idea of an intrastate discursive lens to analyze moral fields constructed by politicians, oriented toward winning support from the public at large.